Corporate Social Responsibility e corporate governance: quale nesso nelle PMI? - Del Baldo, Mara (Piccola Impresa / Small Business, 2009)
The study proposes to individuate the relationship between social engagement, socialstatements and governance of SMEs focusing attention on the elements of the trinomialmission-corporate governance-accountability and on their reciprocal relations. Doesa positive relationship between the adhesion to a culture of social responsibility andgovernance exist? This paper winds itself around this question and describes the principlefindings that have emerged from the qualitative investigation focused on a selected groupof “cohesive” Italian SMEs belonging to the Marches Region, in which the nexus betweenthe evolution of corporate governance and socially responsible management practices wereexamined.The central hypothesis is that in the presence of a solid ethical framework, which ispromoted and shared by the entrepreneurs and managers who guide the business incarrying out socially responsible practices and towards adopting methods communicatingthem (such as a charter of values, a code of ethics, social report, etc.), the arrangement andquality of governance can mitigate tensions and dedicate more energy towards the good ofthe business, of its workers, and of the society and environment in which it operates.The work is articulated in three principle parts. The first section traces its theoreticaland empirical context. The second provides a description of the methodology, describes andinterprets the principle findings that have emerged from the qualitative investigation. Thelast section closes the paper with final remark. The concluding reflections trace the featuresof a territorial model of socially responsible orientation centered on the best practices ofSMEs who are excellent examples of “spirited businesses” and “champions of CSR”